#TITLE_ALTERNATIVE# - ARFAN (NIM 12104057); Pembimbing : Prof. Dr. Irwandy Arif, M.T. dan Dr. Rudianto Ekawan, S, MOCHAMMAD
PT XYZ is a coal mining company which its operation located in Tenggarong, Samarinda, East Kalimantan. Its mining is operated by six contractors with contract system. Its system is single rate and double rate system. Both systems and its value contracts have important role in fixing Break Event Stripping Ratio (BESR) value. That BESR value can be used to analyze the exact Stripping Ratio (SR) target. Those six contractors have not been able to attain production target and often pass over the SR target that has been agreed before, therefore it is needed to do the contract study with possible SR. The economic BESR simulation study results for each subcontractor are 14.52 (A), 15.54 (B), 22.01 (C), 9.17 (D), 7.79 (E) and 13.30 (F), with their varying SR targets from 10 to 14.96 which constitute implication from actual SR that possible in mining company (between 10-14, because it constitutes the remainder deposit that spreads). Only Contractor E which its achievement almost reach the production target. The contractor D and E targeted SR values that pass over BESR value possibly caused by their less appropriate contract value. It is necessary to do contract value evaluation for Contractor C of its big BESR value compared to others and its BESR value that pass over possible mining SR limit. Contractor B's SR targeted value is already appropriate for its value is slightly beyond BESR calculated value, yet its work is bad for its production is far beyond the target and its actual SR is far over the targeted SR and BESR. SR targets for Contractor A and Contractor F have to be increased, at least until they reach their actual SRs, because the values are still far beyond their BESR values, followed by increasing their contract values so that both BESR values are in one level with SR targets that are wanted in order to motivate Contractor A and F so their works increase. Validation result from BESR simulation model with visual basic 6.0 shows that its calculated BESR value application equals manual calculation result, so the program can be used for that kind calculation or case.